Antarctobius bidentatus - Morrone, Juan J. (Zenodo, 2011)
Antarctobius bidentatus (Champion, 1918) Hypera bidentata Champion, 1918a: 176 (type locality: Argentina: Falkland Islands (Islas Malvinas), East Island; type material: H: BMNH). Listroderes (Antarctobius) bidentatus; Kuschel, 1955: 289. Antarctobius bidentatus; Morrone, 1992a: 6. Distribution. Falkland Islands (Islas Malvinas) (Morrone, 1992a; Posadas, 2008). : Published as part of Morrone, Juan J., 2011, Annotated checklist of the tribe Listroderini (Coleoptera: Curculionidae: Cyclominae) 3119, pp. 1-68 in Zootaxa 3119 (1) on page 15, DOI: 10.11646/zootaxa.3119.1.1, http://zenodo.org/record/5246257 : {"references": ["Champion, G. C. (1918 a) The Coleoptera of the Falkland Islands. The Annals and Magazine of Natural History, series, 9, 1, 167 - 186.", "Kuschel, G. (1955) Nuevas sinonimias y anotaciones sobre Curculionoidea (1) (Coleoptera). Revista Chilena de Entomologia, 4, 261 - 312.", "Morrone, J. J. (1992 a). Revision sistematica y analisis cladistico del genero Antarctobius Fairmaire (Coleoptera: Curculionidae). Neotropica, 38, 3 - 20.", "Posadas, P. (2008) A preliminar overview of species composition and geographical distribution of Malvinian weevils (Insecta: Coleoptera: Curculionidae). Zootaxa, 1704, 1 - 26."]}